2012
DOI: 10.1111/j.1753-0407.2012.00187.x
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant activity and protection of pancreatic β‐cells by embelin in streptozotocin‐induced diabetes

Abstract: Objectives:  The aim of the present study was to evaluate the antioxidant potential of embelin in streptozotocin‐induced diabetes. Methods:  Diabetes was induced in rats fasted overnight by the administration of a single dose of streptozotocin, and analyzed for blood, serum, and biological and histological pancreatic tissue parameters in intact control, diabetic, and embelin‐treated diabetic rats (n = 9) at the dose levels of 15, 25, and 30 mg/kg/day for 21 days. Results:  Diabetes caused highly significant ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
41
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(46 citation statements)
references
References 33 publications
(46 reference statements)
5
41
0
Order By: Relevance
“…Similar results have also been reported in the different animal models [44, 45]. The activities of pancreatic antioxidative enzymes (GPx and SOD) are known to be diminished in the islet cells of diabetic animals as β cells are considered to be low in antioxidant defense and susceptible to oxidative stress [46, 47].…”
Section: Discussionsupporting
confidence: 77%
“…Similar results have also been reported in the different animal models [44, 45]. The activities of pancreatic antioxidative enzymes (GPx and SOD) are known to be diminished in the islet cells of diabetic animals as β cells are considered to be low in antioxidant defense and susceptible to oxidative stress [46, 47].…”
Section: Discussionsupporting
confidence: 77%
“…Embelin, one of the phytochemicals, has already been known to have various medicinal effects on diabetes (28,29), ischemia (30), antibacterial activity (31), osteoclastogenesis (32), and several types of cancer such as pancreatic cancer (17), prostate cancer (33), leukemia (34), hepatoma, and colon cancer (18). In the present study, we evaluated the potential of embelin as a therapeutic agent for another fatal disease, malignant glioma.…”
Section: Embe Lin Represses Proliferation Of Human Glioma Cellsmentioning
confidence: 99%
“…Such effect may be explained in part by either a decrease in the rate of intestinal glucose absorption [15] or an increase in peripheral glucose utilization. Some authors have suggested an increased catabolism of glucose due to glucose transporter type 4 translocation to the plasma membrane in muscle and brown adipose cells [16] with up-regulation of the uncoupling protein-1 in brown adipose tissue and hepatic gluconeogenesis [15,17] occurring as a result of hyperinsulinemia or the enhancement of peripheral glucose utilization [16,18] as plausible mechanisms of action. Moreover, a possible stimulatory mechanism on the few surviving β -cells has been considered, which could allow the release of more insulin [19] .…”
Section: Treatmentmentioning
confidence: 99%